2004
DOI: 10.1191/0265532204lt273oa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an in-depth vocabulary knowledge measure for assessing reading performance

Abstract: The central purpose of this study was to empirically evaluate an in-depth vocabulary knowledge measure in the context of developing the new TOEFL test. The study was carried out with a sample of 207 international students attending an intensive English as a second language (ESL) program in a major Canadian university, in order to determine whether this vocabulary knowledge measure could provide a basis for developing appropriate and useful item types for assessing test-takers’ reading comprehension. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 15 publications
1
140
0
4
Order By: Relevance
“…A number of empirical studies have been conducted to examine the relative importance of size versus depth and speed in terms of predictive powers of L2 skills. Qian and Schedl (2004) investigated vocabulary knowledge and reading comprehension among 207 L2 learners of English at intermediate and advanced levels, and reported that 57% of variance of L2 reading scores was explained by size, with an additional 4% of variance explained by depth. A similarly large variance (54%) predicted solely by size was indicated by Qian (2002), with an additional 13% explained by depth (n = 217).…”
Section: A Vocabulary Knowledge and Its Predictive Powermentioning
confidence: 99%
“…A number of empirical studies have been conducted to examine the relative importance of size versus depth and speed in terms of predictive powers of L2 skills. Qian and Schedl (2004) investigated vocabulary knowledge and reading comprehension among 207 L2 learners of English at intermediate and advanced levels, and reported that 57% of variance of L2 reading scores was explained by size, with an additional 4% of variance explained by depth. A similarly large variance (54%) predicted solely by size was indicated by Qian (2002), with an additional 13% explained by depth (n = 217).…”
Section: A Vocabulary Knowledge and Its Predictive Powermentioning
confidence: 99%
“…Qian and Schedl (2004) regard vocabulary as a multidimensional knowledge consisting of depth and breadth. Some researchers such as Schmitt and Meara (1997) and Wesche and Paribakht (1996) noted that to consider merely the breadth of vocabulary knowledge is not of much value since it ignores the more important aspect of word knowledge and that words can be known for a greater or lesser extent.…”
Section: Depth Of Vocabulary Knowledgementioning
confidence: 99%
“…For assessing the participants' depth of vocabulary knowledge the students were required to ISSN 2325-0887 2015 take the depth of vocabulary knowledge test (DVKT), developed by Qian and Schedl (2004). This test consists of two parts the first of which is related to polysemy and synonymy, and the second to collocations.…”
Section: Dvktmentioning
confidence: 99%
See 1 more Smart Citation
“…This test was administered to measure the test-takers' ability to comprehend texts using both cognitive and metacognitive strategies. Qian and Schedl (2004) reported that internal reliability of the test was 0.90 for various native language backgrounds. The test included five reading passages followed by 26 multiple-choice items in total.…”
Section: Methodsmentioning
confidence: 99%